P-003 Clinical and imaging outcomes of patients with acute ischemic stroke and low nihss treated with endovascular therapy. (23rd July 2017) - Grossberg, J; Rebello, L; Bouslama, M; Haussen, D; Frankel, M; Nogueira, R
Abstract : Background: The minimal stroke severity justifying endovascular intervention remains elusive; however, a significant proportion of patients presenting with large vessel occlusions and mild symptoms subsequently decline and have poor outcomes. We aimed to evaluate clinical outcomes of patients presenting with mild symptoms (NIHSS≤8) undergoing endovascular therapy. Methods: Retrospective analysis of a prospectively collected ET database between September/2010-March/2016. Patients with mild symptoms (baseline NIHSS ≤8) were included in the analysis. Primary and secondary efficacy outcome included the rates of good outcome (90 day mRS 0–2) and successful reperfusion (mTICI 2b-3), respectively. Safety outcome was accessed by rates of any parenchymal hematoma (PH-1 and PH-2) and 90 day mortality. Results: 72 patients with baseline NIHSS ≤8 we included in the analysis. Mean age in the overall cohort was 63.3 years (range, 56–69) and 39 patients were men (54%). The mean baseline NIHSS, CTP core volumes, and ASPECTS were 6.3±1.5, 7.5±16.1 cc, and 8.5±1.3 respectively. A total of 28 patients (38%) received intravenous tPA. The occlusions were located as follows: proximal MCA-M1 in 29 (40%), MCA-M2 in 20 (27%), ICA terminus in 6 (8%) and vertebrobasilar in 9 patients (12%). Tandem occlusion was documented in 7 patients (9%). Successful reperfusion (TICI 2b-3) was achieved in 67 patients (93%) and 90 day good outcome (mRS 0–2) in 52 (72%). The mean final infarct volume was 32.2±59.9 cc. Any parenchymal hematoma occurred in 4 patients (5%). The 90 day mortality was 9% (n=7). Logistic regression showed that only successful reperfusion (OR 27.7; 95% CI [1.1–655.5]; p=0.04) was an independent predictor of good outcomes. Conclusion: Our findings demonstrate a good safety profile for endovascular therapy in patients presenting with low NIHSS and proximal arterial occlusions. Future prospective controlled studies are warranted. Disclosures: J. Grossberg: None. L. Rebello: None. M. Bouslama: None. D. Haussen: None. M. Frankel: None. R. Nogueira: None.